Efeito da amoxicilina e do fluoreto no desenvolvimento do esmalte dentário de ratos - Souza, Juliana Feltrin [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Background: Amoxicillin use in early childhood has been associated with molarincisor hypomineralization. Moreover, it has been supposed an association between amoxicillin and fluoride on enamel defects. Aim. This study aimed to evaluate in vivo the effect of amoxicillin and amoxicillin associated with fluoride on the enamel development of rat tooth. Materials and Methods: The research was divided into three studies. Chapter 1 – Fifteen pregnant Holtzman rats (Rattus norvegicus albinus) were divided randomly into three groups to receive saline (SG), 100 mg/kg/day amoxicillin (A100G), or 500 mg/kg/day amoxicillin (A500G), intragastrically, from days 13 to 22 of pregnancy. Twelve offsprings per group got the same dose until day 12. After 7 and 12 days, the specimens were fixed and embedded in paraffin. In the HEstained sections, the thickness of enamel matrix of upper molar germs was evaluated. Moreover, detection of amelogenin on day 7 and matrix metalloproteinase 20 (MMP - 20) on day 12 by immunohistochemistry were carried out. Chapter 2 - Fifteen rats (Rattus norvegicus, Albinus,Holtzman) were randomly divided into three groups to receive saline (SG), 100 mg/kg/day amoxicillin (A100G), or 500 mg/kg/day amoxicillin (A500G), as described in Chapter 1. Ten offspring per group received the same dose until day 40. The animals were euthanized on day 40. A total of 60 upper incisors and 60 upper first molars from 30 animals were dissected. Calcium (Ca) determination was performed by the compleximetric titration method and phosphorus (Pi) determination by colorimetric analysis using a spectrophotometer at 680 nm. A total of 30 lower first molars from 15 animals were analyzed under X-ray microtomography (XMT). Chapter 3 - Forty rats were, randomly, divided into four groups exposed to fluoride in water (100 ppm (mg F/L) or intragastric administration of amoxicillin (500 mg /kg body weight), according to the...

O uso da amoxicilina durante a primeira infância tem sido relacionado ao desenvolvimento de defeitos de esmalte denominados Hipomineralização Molar-Incisivo (HMI). Ademais, há relatos de possível potencialização dos efeitos do fluoreto no esmalte pela amoxicilina. Objetivo: A proposta do presente estudo foi avaliar o efeito da amoxicilina, e da associação amoxicilina com fluoreto no desenvolvimento do esmalte dentário de ratos. Metodologia: O experimento foi dividido em três capítulos. Capítulo 1 - Quinze ratas prenhas (Rattus norvegicus, albinus, Holtzman) foram aleatoriamente distribuídas em três grupos que receberam, a cada 24 h, dose intragástrica de amoxicilina 100 mg/kg/dia (grupo GA100), amoxicilina 500 mg/kg/dia (grupo GA500) ou soro fisiológico (grupo GS), a partir do 130 dia de prenhez. Após o nascimento, doze filhotes de cada grupo receberam o mesmo tratamento das respectivas mães durante os períodos de 7 dias (n=6) e 12 dias (n=6) de vida. Após a eutanásia, as cabeças dos ratos foram removidas, fixadas e processadas para inclusão em parafina. Os cortes frontais da cabeça exibindo os primeiros molares superiores foram em parte corados com H&E e em parte submetidos à reação imuno-histoquímica para detecção de amelogenina e metaloproteinases da matriz-20 (MMP-20). Os cortes corados com H&E foram utilizados para análise morfológica e mensuração da espessura da camada de esmalte. A imunoexpressão para amelogenina e MMP-20 foram avaliados por análise semiquantitativa (H-score). Os dados foram analisados estatisticamente pelo teste Tukey com nível de significância de 5%. Capítulo 2 - Quinze ratas prenhas (Rattus norvegicus, albinus, Holtzman) foram aleatoriamente distribuídas em três grupos, que receberam, amoxicilina 100 mg/kg/dia (grupo GA100), amoxicilina 500 mg/kg/dia (grupo GA500) ou soro fisiológico (grupo GS), conforme descrito no capítulo 1. Após o na...
Keywords: Esmalte dentário; Amoxicilina; Rato; Amoxicillin